Level of Early childhood Independence in Learning During the COVID-19 Pandemic in PAUD - Nurhafani, Meilenia; Sumanto, Reni Pawestuti Ambari (BELIA: Early Childhood Education Papers, 2022)
The COVID-19 outbreak which became a pandemic in Indonesia caused a shift in the form of learning activities. Learning activities during the pandemic are carried out online to reduce the risk of transmission of COVID-19. This study aims to determine the level of independence of early childhood learning during the COVID-19 pandemic in PAUD Patikraja District. The level of independence studied is based on age, parent work groups and facilities and learning infrastructure. The approach used in this study was descriptive quantitative with the type of survey. The subjects in this study were PAUD students with an age range of 4-6 years. The sampling technique uses sampling quota retrieval technique. The total population is 828 learners. The sample used was 270 respondents from nine PAUD in Patikraja District. Data collection techniques were carried out with questionnaires and documentation. Quantitative data analysis was performed using descriptive percentages. The results showed that there were differences in the level of independence based on age aspects, parental work groups, and facilities and infrastructure. In the age aspect, the level of independence of 63.64% of respondents aged 4 years is quite good; 43.02% of 5-year-olds are categorized as good and 53.76% of 6-year-olds have a good level of independence. In the aspect of the parent work group, 38.10% of respondents from group I had a good level of independence; 50.00% of group II respondents were categorized as excellent; 43.43% of respondents from group III were well categorized; 45.45% of respondents from group IV were categorized as good and 60.75% of respondents from group V were categorized as good. In the aspect of infrastructure, the level of independence of 42.45% of respondents with incomplete facilities and infrastructure is very good category; 44.66% of respondents with fairly complete infrastructure with good categories and 72.13% of respondents with complete infrastructure with good categories. Keywords: Early childhood learning, independence, learning during pandemic